2020
DOI: 10.3390/insects11090615
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Native Parasitoids of Fall Armyworm Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Mozambique

Abstract: The alien invasive insect pest Spodoptera frugiperda Smith (Lepidoptera: Noctuidae), commonly referred to as fall armyworm (FAW), is causing significant losses to maize production in Africa since its detection in 2016. As an emergency response, governments in several countries distributed and/or promoted massive use of synthetic insecticides among smallholder farmers to fight FAW. The inappropriate use of synthetic insecticides by non-trained and ill-equipped farmers raises environmental and health concerns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
1
31
2
Order By: Relevance
“…The overall level of parasitism by the different parasitoids was generally low, averaging 9.2%. This compares with the 9.5% parasitism of FAW reported in Mozambique [ 83 ]. The parasitism rate by Che.…”
Section: Discussionsupporting
confidence: 59%
“…The overall level of parasitism by the different parasitoids was generally low, averaging 9.2%. This compares with the 9.5% parasitism of FAW reported in Mozambique [ 83 ]. The parasitism rate by Che.…”
Section: Discussionsupporting
confidence: 59%
“…Presently, little information is available on natural enemies of the fall armyworm in Africa (21) and Asia (22). Although, some recent studies reported natural enemies of fall armyworm in Tanzania, Kenya and Ethiopia (15), Senegal (18), Benin, Ivory Coast and Ghana (17,21,23), Niger (24), Mozambique (25) and India (4,20,22). These studies indicated that the natural enemy complex associated with fall armyworm varies between countries, even though some species (i.e., Coccygidium spp., Chelonus spp., Campoletis spp., Metopius spp., Trichogramma spp., Telenomus sp., Hexamermis sp.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, species in the genus Chelonus that were reported to have wide geographical distribution in the Americas [74] and Australia [75], has equally been documented in some parts of Africa (Uganda, Benin, Ghana, etc). In the case of egg parasitoids parasitism of up to 64% were observed in Niger following augmentative release of T. remus in sorghum fields [76]. Larval parasitism is still low averaging 9.2 and 9.5% in Uganda and Mozambique, respectively [70,72].…”
Section: Biological Control Of Faw In Africamentioning
confidence: 99%